1998
DOI: 10.1161/01.hyp.32.1.108
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Malnutrition-Induced Changes in Blood Pressure

Abstract: Abstract-A link between prenatal malnutrition and hypertension in human populations has recently been proposed. Rat models of prenatal malnutrition have provided major support for this theory on the basis of tail-cuff measurements. However, this technique requires restraint and elevated temperature, both potential sources of stress. To determine the effect of prenatal protein malnutrition on blood pressure under nonstress conditions, 24-hour radiotelemetric measurements were taken in the home cage. Male rats b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(19 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…This suggests elevations in blood pressure following DEX exposure may only be apparent in slightly “stressed” animals, which may be due in part to alterations in the hypothalamic-pituitary-adrenal axis (HPA). Certainly, in studies in the maternal protein restriction rat model it has been shown, when telemetry was used to measure blood pressure, that there were no differences in blood pressure in the intrauterine-growth restricted offspring but the offspring did demonstrate an elevated blood pressure in response to a restraint stress [28], [29]. This could account for the reported elevations in blood pressure in this model when blood pressure was measured using the tail-cuff method in unconditioned restrained rats.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…This suggests elevations in blood pressure following DEX exposure may only be apparent in slightly “stressed” animals, which may be due in part to alterations in the hypothalamic-pituitary-adrenal axis (HPA). Certainly, in studies in the maternal protein restriction rat model it has been shown, when telemetry was used to measure blood pressure, that there were no differences in blood pressure in the intrauterine-growth restricted offspring but the offspring did demonstrate an elevated blood pressure in response to a restraint stress [28], [29]. This could account for the reported elevations in blood pressure in this model when blood pressure was measured using the tail-cuff method in unconditioned restrained rats.…”
Section: Introductionmentioning
confidence: 82%
“…The development of hypertension in adult life after prenatal exposure to glucocorticoids is a common finding [18], [26], [36], [43], [51], although this is not always the case [27], [52], [53]. In this regard, it is important to note that the use of methods such as tail-cuff plethysmography or carotid cannulation to measure blood pressure, may elicit a stress response and thus not truly reflect elevations in basal blood pressure [28], though repeated handling and conditioning of the animal through multiple, repeated measurements made by experienced experimenters may minimize the effects of these stresses and still yield valuable data. Other factors such as recovery from anesthesia, or preheating of the tail have the potential to lead to physiological alterations in the animal's cardiovascular system and a subsequent a rise in blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical data from our laboratory have demonstrated increased behavioral reactivity under stressful conditions in prenatally malnourished rats nutritionally rehabilitated after birth (Duran et al, 2006; Rosene et al, 2004; Tonkiss et al, 1998). Further, in our study of early immediate genes, exposure to restraint stress resulted in a significantly greater number of c-Fos positive neurons in the medial prefrontal and anterior cingulate cortices of adult rats with histories of early protein malnutrition relative to well-nourished controls (Rosene et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…A study in normotensive WKY and hypertensive SHR showed that SBP was approximately 30 mm Hg higher when measured by tail-cuff [WKY, 162 ± 5; SHR, 207 ± 5, mm Hg] than by telemetry [WKY, 131 ± 1; SHR, 178 ± 6, mm Hg] [85]. A study in prenatally malnourished rats showed that the blood pressure increase induced by a noxious odor was augmented by the stress of the tail-cuff procedure itself [86]. The stress from tail-cuff can also affect the response to drugs.…”
Section: Introductionmentioning
confidence: 99%
“…The stress from tail-cuff can also affect the response to drugs. Hydralazine had an approximately 2-fold greater hypotensive effect on the SBP when measured by tail-cuff compared to telemetry, indicating that the antihypertensive effects of some drugs may be influenced by the level of stress the animal is experiencing [86]. Sullivan et al [87] showed that female endothelin B receptor-deficient rats maintained on a HS (8%) diet for two weeks had 12 mm Hg higher SBP than males when measured by tail-cuff; however, in a later study when radiotelemetry was used to measure MAP in these animals, the females no longer had higher blood pressure than the males (David M. Pollock, personal communication).…”
Section: Introductionmentioning
confidence: 99%